The Christos and Caligula’s Statue - Drews, Robert (2024)
The Jerusalem ekklesia of Iesous Christos appears to have provoked Caligula into ordering that his statue be placed in the Jerusalem temple.
Keywords: origin of Christiani name; Claudius’s expulsion of Judaeans from Rome; Agrippa’s imprisonment of Peter; Agrippa’s execution of James; Caligula’s statue